Networked Educational Design for Novice Principals’ Professional Development: Insights from Sweden - Sahlin, Susanne; Sundgren, Marcus (Proceedings of the International Conference on Networked Learning, 2024)
This paper focuses on professional development for school principals, drawing on literature on the education of leaders and school leaders' development. The Swedish National Principal Training Programme (NPTP) is a state-regulated executive education for professional principals in preschools, schools, and school-age Educare centres. It has been mandatory for all newly appointed principals in Sweden since 2010. The NPTP is a mandatory in-service programme and consists of three courses: school law and governance, governing with objectives and results, and school leadership. The programme runs over three years, parallel to working full-time as a principal. The participants are expected to spend 20% of their working time on their studies. The NPTP uses a networked educational design, which is a valuable research topic from a networked professional learning perspective. This pilot study aims to explore the role of networked educational design for novice principals' professional development and strengthened professional confidence and identity. The research question that frames the study is: In what ways do novice principals' experiences of professional development contribute to the development of their professional confidence and identity with a networked educational design? The study employed a qualitative case-study design with a purposive sampling method to include novice principals undertaking Sweden's national school training programme. Data were collected during 2018-2022 from post-programme evaluations, including individual digital questionnaires with close-ended and open-ended responses and small group oral evaluations documented in a log book. The participants were novice principals studying in the NPTP at one university in Sweden. In all, 321 school leaders from 10 cohort groups in the programme consisting of principals and deputy principals from preschool, primary, secondary, and adult education participated voluntarily. The programme evaluations were carried out during the participants' last residential stay in the programme. Results indicate the importance of residential stays and networking opportunities in the educational journey of principals. These opportunities help connect with peers, establish contacts, and acquire valuable strategies. Completing the training increased principals' professional confidence, particularly in their roles as school leaders. The study shows that the networked educational design supports the development of a professional network among principals, which enhances their professional identity and confidence. The COVID-19 pandemic has highlighted the importance of this networked educational design, which helps shape principals' professional identity and confidence. The findings emphasise the value of networked professional learning.